Indonesian Adaptation and Validation of the Inventory of Romantic Relationship Competence among Emerging Adults - Nasma Sania; Pradipta Christy Pratiwi (Bulletin of Social Studies and Community Development, 2026)
Romantic relationships are a form of interpersonal relationship that requires specific skills to build and maintain healthy connections. The Inventory of Romantic Relationship Competence (IRRC; Faber et al., 2019) was developed with seven dimensions to assess emerging adults' perceived romantic competence. However, a formal Indonesian adaptation of the IRRC that examines its psychometric properties is not yet available. This study aims to conduct an initial adaptation and test the construct validity and reliability of the Indonesian version of the IRRC. The instrument, consisting of 35 self-report items on a 5-point Likert scale, was completed by N = 406 participants (aged 18–25 years; active undergraduate students in Indonesia; with diverse romantic relationship statuses and experiences). Confirmatory Factor Analysis (CFA) using JASP indicated that the Indonesian version of the IRRC has good internal reliability across all subscales and that the instrument's validity is adequate and acceptable. Overall, the IRRC is considered valid and reliable, with potential for use in both research and clinical assessment.